2018
DOI: 10.1016/j.bmc.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and NF-κB and mitochondrial transmembrane potential inhibitory pentacyclic triterpenoids from Syzygium corticosum and their semi-synthetic derivatives

Abstract: Syzygium is a large genus of flowering plants, with several species, including the clove tree, used as important resources in the food and pharmaceutical industries. In our continuing search for anticancer agents from higher plants, a chloroform extract of the leaves and twigs of Syzygium corticosum collected in Vietnam was found to be active toward the HT-29 human colon cancer cell line. Separation of this extract guided by HT-29 cells and nuclear factor-kappa B (NF-κB) inhibition yielded 19 known natural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…A recent review report elegantly explains the context-dependent role of autophagy on cancer [14]. The modulation of autophagy, or the molecules involved in the signaling pathways that trigger autophagy, could be targets for investigating and discovering new anticancer agents [15,16]. In that perspective, it has been reported that ursolic and oleanolic acids stimulate autophagy in cancer cells [3,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review report elegantly explains the context-dependent role of autophagy on cancer [14]. The modulation of autophagy, or the molecules involved in the signaling pathways that trigger autophagy, could be targets for investigating and discovering new anticancer agents [15,16]. In that perspective, it has been reported that ursolic and oleanolic acids stimulate autophagy in cancer cells [3,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The freeze dried fruit pulp also induced cell death in different breast cancer cell lines (MCF-7, MCF-10A, and MDA-MB-231) [ 21 ]. Ren et al [ 22 ] studied the NF-κB and mitochondrial transmembrane potential inhibitory effects of ursolic acid (31 nM) isolated from S. corticosum . All these study reports reveal the cytotoxic properties of phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies had reported that triterpenoids have potential antitumor activity, including examples of lupane-, oleanane-, and ursane-type triterpenoids. Previous studies had confirmed that ursane-type triterpenoids have extensive anti-inflammatory, antibacterial, antifungal, and antitumor activities [45][46][47][48]. However, the antitumor effect of ursane-type triterpenoids from the F. palmata had not been reported, especially the anticervical cancer effect of ursane-type triterpenoid compound 10.…”
Section: Cytotoxicmentioning
confidence: 99%